SHARĪ‘AH APPLICATION MODEL IN MUSLIM COUNTRIES - Maghfirah Maghfirah (Pascasarjana UIN ANTASARI Banjarmasin, 2021)
In the Islamic world, leadership is khilāfah for Sunnis and Imāmat for Shiites. Along with the collapse of the Umayyad Empire, Europe, and colonization of the Muslim world, new concepts came into contact, such as the nation-state, democracy, nationalism, etc. In this mixing of ideas, there is a change in the development of the application of sharia. This paper aims to explain sharī‘ah application model in Muslim countries. This paper is a literature review that analyzes reference sources from journals, books, and websites using collecting data in the documentation and various articles and books with content analysis, namely by analyzing descriptive literature data or scientific research’s message. At the same time, the data analysis method is deductive, inductive, and comparative. The findings of this paper are the application of sharī‘ah in the context of modernity in various Muslim countries. There are at least three types of responding to new concepts that are in direct contact with post-colonialism. First, the application of sharī‘ah mixed into the constitution of a country as a whole. Second, sharī‘ah is a sub-ideology, the intersection between religion and the State. Third; is the separation of sharī‘ah and the State. The application of sharī‘ah has many factors, such as the majority of schools, the hegemony of power, and welfare. Thus, in choosing the application of sharī‘ah, there are three forms of understanding, namely ifrāṭ, tafrīṭ, and mu‘tadil.